If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 5n + 2(3n + -7) + -3 Reorder the terms: 0 = 5n + 2(-7 + 3n) + -3 0 = 5n + (-7 * 2 + 3n * 2) + -3 0 = 5n + (-14 + 6n) + -3 Reorder the terms: 0 = -14 + -3 + 5n + 6n Combine like terms: -14 + -3 = -17 0 = -17 + 5n + 6n Combine like terms: 5n + 6n = 11n 0 = -17 + 11n Solving 0 = -17 + 11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11n' to each side of the equation. 0 + -11n = -17 + 11n + -11n Remove the zero: -11n = -17 + 11n + -11n Combine like terms: 11n + -11n = 0 -11n = -17 + 0 -11n = -17 Divide each side by '-11'. n = 1.545454545 Simplifying n = 1.545454545
| 13-3r+2+6r-2r-1=3+2-7 | | 3.00+0.80x+4.50=27.50 | | x^2-6x+22=0 | | 15=-3/2x | | 63-7x=21 | | 4/9x=12 | | 2(5x-25)=10(x+5) | | -2/n+4-n^2/n^2-16 | | y^-3*y^-4*y^0/(3y^-2)^3 | | 1-10n=-2+35 | | 1/2(y+6)+4=1/6(9y-30)-3 | | -7*(-35)+5y=-35 | | 28=8n | | 24.95(2)+0.29X=100 | | -7*7+5y=-35 | | 64p^6-27q^3=0 | | t+1/2=2t+8/3 | | 6x*14=12000 | | t+1/2 | | 18-4x=-8x+6 | | 6s+60=12s | | 7(y+2)+y=4(y+3)-2 | | 4+9t-1=6t+66-4t | | (5x/x-1)+(2/x)=6 | | k/7+10=0 | | 4x^5+40x^3+36=0 | | 8/3x=-24 | | 6a^2+17a+10=0 | | -2d^5+24d^2=0 | | 7(x-5)+8=0 | | -5x+13=12 | | 1/2(y+5)+3=1/4(7y-11)-8 |